Pamirian crossroads Kirghiz and Wakhi of High Asia - Kreutzmann, Hermann (Harrassowitz Verlag, 2015)
Mapping the Pamirs and Wakhan mountain areas in High Asia, the author researches marginal border areas of Afghanistan, Pakistan, China and Tajikistan and how they were used by the Kirghiz and Wakhi peoples over time. Both archival and published textual, photographic and cartographic resources are used to illustrate this exploration of remote Asian mountain areas in the context of boundary-making, crossroads, communities, and migration.